Factors Associated with JKN Premium Payment Compliance Among PBPU Participants in Jambi City - Leni Novita Sari; Dwi Noerjoedianto; M Ridwan M Ridwan; Budi Aswin; Ashar Nuzulul Putra (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Compliance with National Health Insurance premium payments is essential for ensuring the sustainability of Indonesia's health insurance system. However, many independent participants fail to pay premiums on time. Objective: This study aimed to identify factors associated with premium payment compliance among Non-Wage Recipient Participants in Jambi City. Method: A quantitative cross-sectional study was conducted among 106 participants selected through random sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics and the Chi-square test with a significance level of 0.05. Results and Discussion: Employment, knowledge, income, payment method, history of catastrophic disease, perceptions of healthcare services, and family support were significantly associated with premium payment compliance. Participants with stable employment, better knowledge, higher income, convenient payment methods, positive healthcare service perceptions, a history of catastrophic disease, and stronger family support were more likely to comply with premium payments. These findings indicate that compliance is influenced by multiple socioeconomic, behavioral, and healthcare-related factors. Conclusion: Strengthening health education, improving healthcare service quality, expanding accessible payment channels, and increasing family support may enhance premium payment compliance and contribute to the sustainability of the National Health Insurance program